Judicial Work in the Modern Technological Era: Interaction of Law with Science Fiction Technology - BOUAMRA, Okba (Journal of Human Sciences, 2025)
Rapid technological changes have profoundly transformed legal practices and judicial procedures, through the interaction of law with science fiction technologies in the era of artificial intelligence. This has had a widespread impact on the judicial system. This research aims to explore the trend towards “smart justice” within the framework of modern experiments and practices that have employed intelligent technologies to enhance the efficiency and effectiveness of judicial and legal work. This includes examining both the advantages and disadvantages. The research uses a descriptive, analytical, and comparative approach to understand the mutual influences between technology and law, and how to leverage them to improve judicial practices. It also seeks to forecast the reality of judicial and legal work facing rapid technological development, and to propose ways for the judicial system to benefit from science fiction technologies in a manner that serves justice and the public interest.